2020
DOI: 10.3390/molecules25092178
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Bio-Based Organic UV-A and Blue Light Filters from Meldrum’s Acid

Abstract: Faced with the ban of some organic UV filters such as octinoxate or avobenzone, especially in Hawaii, it became essential to offer new alternatives that are both renewable and safe for humans and the environment. In this context, a class of bio-based molecules displaying interesting UV filter properties and great (photo)stability has been developed from Meldrum’s acid and bio-based and synthetic p-hydroxycinnamic acids, furans and pyrroles. Moreover, p-hydroxycinnamic acid-based Meldrum’s derivatives possess v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…It has been observed that the presence of methoxy substituents (-OMe) on the aromatic ring significantly decreased the interaction of molecules with endocrine receptor [46], therefore, the use of a sinapic acid core that possesses two -OMe substituents should result in a lower risk of endocrine disruption. Moreover, previous studies in our laboratory proved the innocuousness of several sinapic acid derivatives towards endocrine receptors [47,48]. However, while the sinapic core seems favorable with regards to human health, the impact of the ester moiety on the latter, as well as the possible environmental toxicity of these compounds, should not be overlooked.…”
Section: Loss Of Absorbance (Loa)mentioning
confidence: 71%
“…It has been observed that the presence of methoxy substituents (-OMe) on the aromatic ring significantly decreased the interaction of molecules with endocrine receptor [46], therefore, the use of a sinapic acid core that possesses two -OMe substituents should result in a lower risk of endocrine disruption. Moreover, previous studies in our laboratory proved the innocuousness of several sinapic acid derivatives towards endocrine receptors [47,48]. However, while the sinapic core seems favorable with regards to human health, the impact of the ester moiety on the latter, as well as the possible environmental toxicity of these compounds, should not be overlooked.…”
Section: Loss Of Absorbance (Loa)mentioning
confidence: 71%
“…The barbiturics were synthesised using a green methodology based on the Knoevenagel condensation in water. The syntheses use no catalyst or organic solvent, thereby improving atom economy, 40,82 and were performed at room temperature, thereby minimising energy consumption. Further, the barbiturics precipitated readily from the reaction medium, enabling their recovery and purification simply by a classic filtration, without recourse to energy-and solvent-consuming, and waste-generating, silica gel chromatography.…”
Section: Synthesismentioning
confidence: 99%
“…(1) applied green chemistry principles to the well-established Knoevenagel and Knoevenagel-Doebner condensation reactions of cinnamates [38][39][40][41] to develop a synthetic route to barbiturics; 38,39,[41][42][43][44][45][46][47][48][49][50][51] (2) explored the photophysical properties of these barbiturics using steady-state and ultrafast transient absorption spectroscopies to gain insight into the light-to-heat generating pathways; (3) complemented these experiments with time-dependent density functional theory (TDDFT) and DFT/multireference configuration interaction (DFT/MRCI) calculations to describe these molecular relaxation pathways more fully; and (4) used in silico approaches to explore the potential toxicity of the barbiturics on humans. 52,53 Experimental and Computational Methods…”
Section: Introductionmentioning
confidence: 99%
“…First, concerning phloretin, its loss of absorbance was 5.9% against 26.0% for octinoxate and only 0.6% for avobenzone. Peyrot et al mentioned in their study that the acceptable absorbance loss to match the commercial UV filters specifications should be less than 5% [ 43 ]. Phloretin’s result was very close to these specifications and revealed itself more photostable than octinoxate.…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosinase inhibition activity was evaluated using the method used by Peyrot et al [ 43 ]. In a 96-well microplate, 60 µL of ammonium formate buffer (50 mM, pH 6.4) were mixed with 10 µL of inhibitor solution at different concentrations: 10,000, 5000, 1000, 500, 100, 50, 10, 5, 1 and 0.5 µM in DMSO.…”
Section: Methodsmentioning
confidence: 99%